Capitalizing a cure : how finance controls the price and value of medicines - Roy, Victor, 1986- (University of California Press, 2023)
"Capitalizing a Cure takes us into the struggle over accessing a medical breakthrough to investigate the power of finance over business, biomedicine, and public health. When sofosbuvir-based medicines launched in 2013, they promised a cure for millions of patients worldwide with hepatitis C. But their sticker shock-the drug was dubbed "the $1,000-a-day pill"-intensified a global debate over the pricing of new medicines. Weaving extensive historical research with insights from political economy and science and technology studies, Victor Roy demystifies an oft-missed dynamic in this debate: the reach of financialized capitalism into how medicines are made, priced, and valued. His account travels between public and private labs, Wall Street and corporate boardrooms, public health meetings and health centers to trace the ways sofosbuvir-based medicines became financial assets dominated by strategies of speculation and extraction at the expense of access and care. Provocative and sobering, this book illuminates the harmful impact of allowing financial markets to supersede democracy and human health and points to the necessary work of building more equitable futures"--